Method for recycling regenerated sodium-based iron sulfate cathode material from waste sodium-ion battery, cathode material and battery

CN122992208APending Publication Date: 2026-10-27NAYUAN NEW MATERIAL TECH (WUXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611048868.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]有鉴于此,本发明的目的是提供从废旧钠离子电池回收再生钠基铁硫酸盐正极材料的方法、正极材料和电池,以至少解决现有技术中存在三价铁还原不彻底和再生过程中易生成杂相的问题

Benefits of technology

(1)本发明针对退役硫酸铁钠基正极片因钠离子不完全脱嵌引发的Fe2+/Fe3+混合价态紊乱、钠元素非化学计量比偏移及晶体结构畸变等真实失效工况精准设计,有效解决了传统回收工艺中三价铁还原受阻、还原不彻底的行业难题。本发明的方法无需限定原料初始铁价态、钠含量及充放电状态,可全面兼容NaFe(SO4)2、Na2Fe(SO4)2、Na2Fe2(SO4)3及各类中间相材料体系,对不同充放电程度的退役硫酸铁钠基正极材料具备通用回收修复能力,还可同步修复电池循环过程产生的晶格缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992208A_ABST
    Figure CN122992208A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery materials, and more particularly to a method for recycling regenerated sodium-based iron sulfate positive electrode material from waste sodium-ion batteries, a positive electrode material and a battery. The present application utilizes the water-soluble characteristics of mixed-valence sodium sulfate iron-based positive electrode material, uses the positive electrode sheet of the completely discharged sodium-ion battery as raw material, realizes the lossless dissolution of sodium, iron and sulfate main elements through pure water leaching; through precise addition of sodium source and iron source calibration liquid phase sodium iron metering ratio, the target crystal chemical ratio is matched; carbon nanotubes / carbon source are introduced to construct a uniform reduction reaction interface and an in-situ carbon conductive network, relying on wet homogenization, spray drying and low-temperature inert sintering process, waste material lattice reconstruction, carbon coating and continuous promotion of residual Fe 3+ oriented reduction to Fe 2+ , while inhibiting the reverse oxidation of newly generated Fe 2+ at all stages. The present application solves the problems of incomplete reduction of trivalent iron and easy generation of impurities in the regeneration process of existing positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and in particular to a method for recovering and regenerating sodium-based ferric sulfate cathode materials from waste sodium-ion batteries, the cathode materials, and the battery. Background Technology

[0002] Sodium ferric sulfate-based cathode materials (including polyanionic iron-based sulfates such as NaFe(SO4)2 and Na2Fe(SO4)2) rely on SO4 2- The high structural stability and moderate operating voltage (3.6-3.7V vs Na) provided by the polyanionic groups + With advantages such as high theoretical specific capacity (110-120 mAh / g), low raw material cost, and environmental friendliness, this type of material has achieved large-scale commercial applications in fields such as grid energy storage, low-speed electric vehicles, and backup power supplies. The crystal structure of this type of material is generally monoclinic. + Located at the interstitial sites of the polyanionic framework, Fe passes through during charging and discharging. 2+ / Fe 3+ Redox couple realizes Na + The reversible insertion and extraction are accompanied by dynamic changes in the iron valence state and real-time fluctuations in sodium content.

[0003] As these sodium-ion batteries enter their retirement phase in large numbers, developing low-cost, environmentally friendly, and efficient recycling technologies that are adapted to the inherent properties of their materials is a core necessity for achieving cost reduction and sustainable development throughout the entire lifecycle of this technology. Existing recycling technologies for these materials, if employing pyrometallurgical or strong acid wet recycling processes used for lithium-ion batteries, have significant technical drawbacks. The direct reason is that recycling methods suitable for lithium batteries are not applicable to sodium ferric sulfate series materials. Specific drawbacks are as follows: (1) Traditional pyrometallurgical recovery requires high-temperature roasting above 600℃, which not only consumes a lot of energy and causes a lot of flue gas pollution, but more importantly, sodium and sulfur have low boiling points and are easily volatilized and lost at high temperatures. At the same time, Fe 2+ It readily undergoes a disproportionation reaction to produce elemental iron and Fe. 3+ Impurities prevent the direct closed-loop regeneration of materials; only crude metal products can be recovered, resulting in extremely low resource utilization.

[0004] (2) Traditional strong acid wet recycling requires leaching with strong acids such as sulfuric acid and hydrochloric acid, followed by extraction, precipitation, crystallization and other multiple steps to separate and purify metal elements. The process involves more than a dozen steps, resulting in high reagent consumption and high cost of treating high-salt wastewater. This is completely unsuitable for the low-cost properties of sodium iron sulfate-based materials. Furthermore, strong acid leaching will simultaneously corrode the aluminum foil current collector, making it impossible to achieve lossless recycling of the current collector.

[0005] To address the aforementioned technical issues, the core idea in existing technologies for pure +2 valent sodium ferrous sulfate systems is to decompose sodium ferrous sulfate into ferrous sulfate and sodium sulfate monosalts in water, and then simultaneously add antioxidants and pH adjusters to inhibit Fe... 2+ Oxidation, followed by sintering to resynthesize the material, has the following drawbacks: ① It cannot adapt to the mixed valence state conditions of actual retired electrode sheets. In real industrial scenarios, retired sodium ferric sulfate-based positive electrode sheets have incomplete sodium ion insertion and extraction during charge-discharge cycles, resulting in a mixed valence state of iron (+2 valence, sodium insertion state) and iron (+3 valence, sodium extraction state). The sodium content is also not in the standard stoichiometric ratio, and the material's crystal structure has undergone local distortion. More importantly, existing technologies for this type of mixed valence material generally suffer from the problem of incomplete or ineffective reduction of ferric iron, leading to residual Fe in the recycled material. 3+ Impurities severely affect the electrochemical performance of materials, and this technology cannot repair crystal structure defects. It can only process fresh, pure-phase materials, resulting in extremely poor industrial applicability.

[0006] ② The process is highly dependent on advanced technology and has high costs. Antioxidants and pH adjusters must be added simultaneously; neither can be omitted, otherwise Fe... 2+ It will quickly oxidize and become ineffective, the reagent cost is high, and a large number of additives will introduce impurity ions, affecting the purity and performance of the recycled materials; ③ The structural irreversibility of the decomposition-resynthesis path forces the material to decompose into a single salt and then resynthesize it, which will destroy the original polyanionic framework structure of the material. Impurities are easily generated during the regeneration process, and the material properties are difficult to restore to the original level.

[0007] In summary, current technologies have not yet developed a method suitable for the mixed valence state of decommissioned electrodes (Fe valence state caused by sodium intercalation). 2+ Fe resulting from sodium removal 3+ It can solve the problem of incomplete reduction of ferric iron (Fe3+) under actual working conditions, and is compatible with sodium-based ferric sulfate systems of all valence states. It also features a closed-loop recycling and regeneration method that can repair crystal structure defects, is low-temperature and low-consumption, has flexible and controllable processes, and is low-cost and environmentally friendly. Furthermore, it provides solutions for various charge / discharge levels (different sodium insertion / extraction degrees, different Fe3+ levels). 2+ / Fe 3+ The current approach to recycling sodium ferric sulfate-based materials (in proportion) cannot meet the core needs of large-scale recycling in the industry. Summary of the Invention

[0008] In view of this, the purpose of the present invention is to provide a method, a cathode material, and a battery for recycling sodium-based ferric sulfate cathode material from waste sodium-ion batteries, so as to at least solve the problems of incomplete reduction of ferric iron and easy generation of impurity phases during the regeneration process in the prior art.

[0009] The following is a summary of this disclosure to provide a basic understanding of some aspects. This summary is not intended to identify key or important elements, nor is it intended to limit the implementation or any aspects of the claims. Furthermore, this summary provides a simplified overview of some aspects that can be described in more detail in other parts of this disclosure.

[0010] The present invention solves the above-mentioned technical problems through the following technical means: In a first aspect, embodiments of this application provide a method for recovering recycled sodium-based ferric sulfate cathode material from spent sodium-ion batteries, comprising the following steps: Waste iron sulfate sodium-based positive electrode sheets were obtained by dismantling fully discharged waste sodium-ion batteries. After pretreatment, sodium iron sulfate was leached out with water, and solid-liquid separation was performed to obtain a homogeneous aqueous solution containing sodium, iron, and sulfate. The iron element in the homogeneous aqueous solution was in a mixed valence state of +2 and +3. To detect the sodium and iron content in a homogeneous aqueous solution, sodium and iron sources are added to the homogeneous aqueous solution according to a molar ratio of sodium to iron of (1.0–2.0):1, and the solution is dissolved to obtain an element calibration solution. A pH adjuster and / or a complexing agent are added to the elemental calibration solution. The pH adjuster is used to adjust the pH of the elemental calibration solution to 2.5–6.5, and the complexing agent is used to complex Fe in the elemental calibration solution. 3+ Forming a crystallization precursor core; and / or, according to the mass fraction of carbon element in the final obtained cathode material being 1% to 5%, adding carbon nanotubes and / or carbon source, ultrasonically stirring and mixing to obtain a regenerated precursor solution; The regenerated precursor liquid was wet-milled to obtain a regenerated slurry with uniform particle size and a solid content of 10% to 40%. The recycled slurry was spray-dried and granulated, sintered at 300–400℃ for 4–24 h in an inert atmosphere, and then crushed and sieved to obtain recycled sodium ferric sulfate-based cathode material.

[0011] The above technical solution addresses two issues: First, in the crystal structure of sodium iron sulfate materials in waste batteries, Na... + With [Fe(SO4)2] n- The polyanionic framework is bonded by ionic bonds, which are relatively weak; under the strong solvation effect of water molecules, Na + It preferentially combines with water molecules to form hydrated sodium ions, which then desolvate from the interstices of the framework and enter the aqueous solution, thereby driving the entire [Fe(SO4)2] group into the solution. n-The polyanionic clusters dissociate and disperse uniformly in the aqueous solution as complexed anions, achieving complete dissolution of the active material. Meanwhile, the aluminum foil current collector forms a dense alumina passivation film on its surface in a neutral aqueous solution, preventing corrosion and dissolution. Therefore, efficient and non-destructive separation of the active material and the current collector can be achieved under mild conditions, completely different from the "decomposition-stripping" path of existing technologies. This preserves the basic structural units of the polyanionic framework, laying the foundation for subsequent crystal structure repair and regeneration.

[0012] Secondly, during the battery charge-discharge cycle, Na... + Irreversible insertion / extraction leads to the formation of numerous sodium vacancies within the material, and some Fe... 2+ Oxidized to Fe 3+ Subsequently, to balance the crystal charge, a small amount of Fe element dissolves and is lost, ultimately causing the material to deviate from the ideal stoichiometry. This results in local distortion and collapse of the crystal structure, which is the core reason for the degradation of the material's electrochemical performance. The technical solution in this application uses liquid-phase quantitative detection to precisely replenish the sodium and iron sources, achieving Na+ at the molecular level in aqueous solution. + Fe 3+ / Fe 2+ SO4 2- The uniform mixing accurately restores the stoichiometry of the material, eliminates sodium vacancies and lattice distortion, avoids the generation of impurity phases during the regeneration process, and ensures that the crystal structure of the regenerated material is completely consistent with that of the original material.

[0013] Third, the technical solution of this application utilizes the intrinsic reducing and conductive properties of carbon nanotubes and carbon sources to achieve Fe 3+ In-situ reduction and conductive network construction are completed in one step, completely replacing existing antioxidant solutions. This thoroughly solves the industry pain point of incomplete or ineffective reduction of ferric iron in actual recycling, while eliminating the need to differentiate between the charge and discharge levels of the raw materials (i.e., different sodium deintercalation and deintercalation levels, different Fe...). 2+ / Fe 3+ The ratio provides a unified recycling approach for sodium ferric sulfate-based recovery materials with various charge / discharge levels. The core mechanism consists of two stages: ① Liquid phase stage: Carbon nanotubes or water-soluble carbon sources are uniformly dispersed in an aqueous solution. The reducing functional groups (such as hydroxyl and carboxyl groups) on their surface can release free Fe. 3+ (The ferric iron produced by sodium removal) is completely reduced to Fe. 2+ (Target valence state of sodium intercalation), precisely controlling the valence state of iron to fundamentally solve the valence imbalance problem of mixed valence states, without the need to add any antioxidants; ② Sintering stage: After spray drying, carbon material is uniformly coated on the surface of precursor particles. In the subsequent sintering process, it continues to play a reducing role, inhibiting Fe 2+Secondary oxidation ensures precise control of the target valence state and avoids residual trivalent iron; on the other hand, pyrolysis and carbonization form a continuous three-dimensional conductive network that uniformly coats the surface of the material grains, which not only significantly improves the electronic conductivity of the material but also inhibits excessive grain growth during sintering and shortens the Na... + The solid-phase diffusion path significantly improves the rate performance and cycle stability of the material.

[0014] Fourth, the use of low-temperature sintering at 300–400℃ perfectly matches the crystallization temperature window of sodium-based ferric sulfate materials. At this temperature, Na… + Fe 2+ SO4 2- It can complete solid-phase diffusion and lattice rearrangement to form a complete polyanionic crystal structure without the generation of impurity phases; at the same time, the pyrolysis and carbonization of the carbon source can be fully carried out in this temperature range to form a uniform and dense amorphous carbon coating layer; it can also effectively avoid sodium volatilization and grain growth, ensuring that the grain size of the recycled material is uniform, the structure is stable, and the electrochemical performance is fully restored to the level of the original material.

[0015] Fifth, in the preparation of the sodium ferric sulfate precursor complex solution, the added organic acids (such as oxalic acid, citric acid, etc.) act as pH adjusters and complexing agents. These organic acids decompose at relatively low calcination temperatures (300-400℃), producing reducing protective gases such as CO and H2, which protect the Fe... 2+ While preventing oxidation, it further promotes Fe 3+ The reduction ultimately yields a complete Fe-containing compound. 2+ The crystalline structure of the battery recyclable sodium-based ferric sulfate cathode material.

[0016] Secondly, embodiments of this application also provide a positive electrode material, which is obtained by the method described in the first aspect. The positive electrode material is a sodium-based ferric sulfate positive electrode material with the general formula Na. x Fe y (SO4) z ·Cw, where 1≤x≤2, 1≤y≤2, and satisfies x+2y=2z, C is the mass fraction of carbon content, and w ranges from 1% to 5%.

[0017] Thirdly, embodiments of this application also provide a positive electrode sheet, the positive electrode sheet comprising the positive electrode material as described in the second aspect.

[0018] Fourthly, embodiments of this application also provide a battery, the battery including the positive electrode as described in the third aspect.

[0019] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages: (1) This invention addresses the Fe ion degradation caused by incomplete sodium ion deintercalation / intercalation in decommissioned sodium sulfate-based positive electrode sheets. 2+ / Fe 3+ The method is precisely designed to address real-world failure conditions such as disordered mixed valence states, non-stoichiometric deviations of sodium, and crystal structure distortions, effectively solving the industry-wide problems of hindered and incomplete reduction of trivalent iron in traditional recycling processes. This invention does not require limitations on the initial iron valence state, sodium content, or charge / discharge state of the raw materials, and is fully compatible with NaFe(SO4)2, Na2Fe(SO4)2, Na2Fe2(SO4)3, and various intermediate phase material systems. It possesses universal recycling and repair capabilities for retired sodium ferric sulfate-based cathode materials with different charge / discharge levels, and can also simultaneously repair lattice defects generated during battery cycling.

[0020] (2) The method of the present invention utilizes the reducing and conductive properties of carbon nanotubes / carbon sources, and combines them with added pH adjusters and complexing agents (such as oxalic acid, citric acid, etc.) to decompose this property at a relatively low calcination temperature (300-400℃), generating reducing protective gases such as CO and H2, which simultaneously achieve Fe production with the aforementioned carbon source. 3+ In-situ reduction and construction of a three-dimensional conductive network of carbon materials completely replace the antioxidant solution of existing technology, fundamentally solves the problem of valence state regulation of mixed valence states, greatly simplifies the process, reduces reagent costs, and introduces almost no impurity ions, ensuring the purity of the recycled materials.

[0021] (3) The method of the present invention uses a low-temperature inert atmosphere sintering at 300-400℃, which can ensure the pure phase crystallization of sodium-based iron sulfate materials and repair the crystal structure, as well as inhibit excessive grain growth and sodium volatilization. At the same time, the pyrolysis carbonization and coating effects of the carbon source can be fully utilized, reducing energy consumption by more than 60% compared with the traditional high-temperature sintering process, and is suitable for large-scale continuous production.

[0022] (4) The method of the present invention uses deionized water as the sole solvent throughout the process, adding only trace amounts of pH adjuster or complexing agent as needed, while protecting Fe. 2+ and Fe 3+ At the same time, there is no need to add antioxidants, no use of strong acids, strong alkalis, or toxic organic solvents, and no high-salt wastewater or organic waste gas emissions. The recycling cost is reduced by more than 50% compared to the traditional wet process, and the aluminum foil current collector can be recycled and reused without damage, with a resource utilization rate of nearly 100%.

[0023] (5) The method of the present invention achieves crystal structure repair through precise feeding in a liquid phase system. The mixing uniformity of each element is good. Finally, the core indicators such as crystal structure, micromorphology, specific capacity, and cycle stability of the regenerated cathode material are comparable to those of the original material. It can be directly recycled in a closed loop to battery preparation, thereby maximizing the utilization of resources. Attached Figure Description

[0024] Figure 1 These are the XRD spectra of the regenerated sodium-based ferric sulfate cathode materials prepared in Examples 1-8 and the cathode material of Comparative Example 1; Figure 2 This is a SEM image of the regenerated sodium-based ferric sulfate cathode material prepared in Example 1; Figure 3 This is a schematic diagram comparing the first charge-discharge curves of the sodium-based iron sulfate cathode material of Example 1 and the cathode material of Comparative Example 1 at a 0.1C rate. Figure 4 This is a schematic diagram showing the rate comparison of sodium-ion half-cells assembled with the sodium-based iron sulfate cathode material of Example 1 and the cathode material of Comparative Example 1 at 2.0~4.3V, 0.1C, 0.2C, 0.5C, 1C, 2C and 5C. Figure 5 This is a schematic diagram of a sodium-ion half-cell assembled from the sodium-based iron sulfate cathode material of Example 1 and the cathode material of Comparative Example 1 under long-term cycling at 2.0~4.3V and 0.2C. Detailed Implementation

[0025] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0026] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0027] Existing technologies for recycling sodium ferric sulfate-based cathode materials have several drawbacks, such as: firstly, they cannot be adapted to the Fe content caused by incomplete sodium ion deintercalation / intercalation in retired electrodes. 2+ (Sodium intercalation) and Fe 3+ (Sodium removal) In actual working conditions with mixed valence states, it cannot repair the crystal structure distortion caused by the cycle, and there are common problems such as the inability to reduce ferric iron or incomplete reduction, resulting in poor adaptability; secondly, it must rely on antioxidants and pH adjusters, which leads to high reagent costs, redundant processes, and easy introduction of impurity phases; thirdly, the decomposition-resynthesis path destroys the polyanionic framework, high-temperature sintering consumes a lot of energy, easily generates impurity phases, and cannot achieve low-cost closed-loop regeneration, etc.

[0028] To address the aforementioned technical problems, this application provides a method for recovering recycled sodium-based ferric sulfate cathode material from spent sodium-ion batteries, comprising the following steps: S1. Disassemble and obtain waste iron sulfate sodium-based positive electrode sheets from fully discharged waste sodium-ion batteries. After pretreatment, add water to leach sodium iron sulfate, and perform solid-liquid separation to obtain a homogeneous aqueous solution containing sodium, iron, and sulfate ions. The iron element in the homogeneous aqueous solution is in a mixed valence state of +2 and +3.

[0029] S2. To detect the sodium and iron content in the homogeneous aqueous solution of step S1, sodium and iron sources are added to the homogeneous aqueous solution according to the molar ratio of sodium to iron of (1.0~2.0):1, and dissolved to obtain the element calibration solution.

[0030] S3. Add a pH adjuster and / or a complexing agent to the elemental calibration solution. The pH adjuster is used to adjust the pH of the elemental calibration solution to 2.5–6.5, and the complexing agent is used to complex the Fe in the elemental calibration solution. 3+ A precursor core for crystallization is formed. And / or, carbon nanotubes and / or a carbon source are added according to the mass fraction of carbon in the final cathode material being 1% to 5%, and the mixture is ultrasonically stirred to obtain a regenerated precursor solution.

[0031] In this step, specifically, in one embodiment, a pH adjuster, a complexing agent, carbon nanotubes, and a carbon source are added to the elemental calibration solution; in another embodiment, only a pH adjuster and a complexing agent are added to the elemental calibration solution; in another embodiment, a pH adjuster, a complexing agent, and carbon nanotubes are added to the elemental calibration solution; in another embodiment, a pH adjuster, a complexing agent, and a carbon source are added to the elemental calibration solution; in another embodiment, a pH adjuster and carbon nanotubes are added to the elemental calibration solution; in another embodiment, carbon nanotubes and a carbon source are added to the elemental calibration solution; in yet another embodiment, a carbon source is added to the elemental calibration solution.

[0032] S4. The regeneration precursor liquid from step S3 is subjected to wet milling to obtain a regenerated slurry with a solid content of 10% to 40% and uniform particle size.

[0033] S5. Spray dry and granulate the recycled slurry, sinter it at 300-400℃ for 4-24 hours under an inert atmosphere, crush and screen it to obtain the recycled sodium ferric sulfate-based cathode material.

[0034] Utilizing the water solubility of sodium iron sulfate, this method uses retired fully discharged sodium-ion battery cathode sheets as raw materials. Sodium, iron, and sulfate ions are dissolved without damage through pure water leaching. The sodium-iron stoichiometry in the liquid phase is calibrated by precisely adding sodium and iron sources to match the target crystal stoichiometry. Added organic acids (such as oxalic acid and citric acid) act as pH adjusters and complexing agents. These organic acids decompose at relatively low calcination temperatures (300-400℃), producing reducing protective gases such as CO and H2. Carbon nanotubes / carbon sources are introduced to construct a uniform reduction reaction interface and an in-situ carbon conductive network. Through wet homogenization, spray drying, and low-temperature inert sintering processes, lattice reconstruction and carbon coating of waste materials are achieved, and residual Fe is continuously promoted. 3+ Directional reduction to Fe 2+ At the same time, it inhibits the formation of new Fe throughout the process. 2+ Reverse oxidation.

[0035] After complete discharge, the discharge cutoff voltage of the spent sodium-ion batteries is controlled at 0.4–0.6V to ensure that there are no residual lithium / sodium intercalation charges inside the negative electrode, avoiding localized polarization and uneven heating during subsequent processing, and ensuring that most sodium ions are intercalated into the positive electrode material through electrochemical reaction. Waste sodium ferric sulfate-based positive electrode sheets are disassembled from the fully discharged spent sodium-ion batteries. The outer shell, separator residue, and electrolyte residue are removed from the waste sodium ferric sulfate-based positive electrode sheets. The surface dust is dried and wiped away to keep the waste sodium ferric sulfate-based positive electrode sheets dry, preventing premature dissolution and the formation of localized slurry agglomeration.

[0036] In some embodiments, the pretreatment of waste sodium ferric sulfate-based positive electrode sheets in step S1 is as follows: The recycled waste sodium ferric sulfate-based positive electrode sheets were activated by simultaneous superposition of a 20-40 kHz ultrasonic field and a 2.45 GHz microwave field for 10-30 minutes, with the activation temperature controlled at 40-60℃ and the activation power density controlled at 50-100 W / L.

[0037] After activation, the positive electrode sheet must enter the water leaching process within 2 hours to avoid the natural closure of the microcrack interface and the secondary re-adhesion of the binder interface after activation, thus maximizing the activation and efficiency enhancement effect.

[0038] The ultrasonic cavitation effect of the ultrasonic field generates instantaneous microjets and shock waves, precisely breaking the interfacial bonding force between the binder and active material inside the positive electrode, weakening the agglomerated encapsulation structure, without mechanical forced wear, and without damage to the aluminum foil current collector substrate. The ultrasonic cavitation and microwave heating occur simultaneously, and the interfacial stripping effect of ultrasonic cavitation is further enhanced by the microwave crystal micro-expansion effect. The 2.45GHz microwave has selective heating characteristics, generating dielectric heating only on iron-sodium sulfate polar crystals, forming uniform nanoscale microcracks inside the crystal without destroying the overall crystal framework structure. This effect is synchronously coupled with ultrasonic cavitation, significantly increasing the subsequent ion permeation rate of aqueous solution, achieving damage-free activation of the positive electrode, and significantly improving the subsequent water leaching efficiency. Furthermore, ultrasonic cavitation breaks down binder encapsulation and particle agglomeration, allowing the internally encapsulated inert Fe... 3+ Complete exposure eliminates the reduction blind zone, creating conditions for subsequent deep reduction; microwave gentle activation of the sodium ferric sulfate lattice enhances Fe... 3+ It increases ionic reactivity and lowers the reduction energy barrier.

[0039] In some embodiments, the homogeneous aqueous solution is prepared in step S1 as follows: The active material of the positive electrode was peeled off from the pretreated waste sodium ferric sulfate-based positive electrode sheet using a mechanical stripping method to obtain coarse positive electrode powder. The coarse positive electrode powder was added to deionized water at 25-40℃ at a solid-liquid ratio of 1 kg: (5-20) L and leached at 100-150 rpm for 20-30 min. The temperature was then raised to 60-80℃ and leached at 250-300 rpm for 90-120 min. The temperature was then lowered to 35-45℃ and leached at 50-100 rpm for 20-30 min. The leachate was allowed to settle and the supernatant was collected to obtain a homogeneous aqueous solution.

[0040] For example, mechanical peeling can be performed using any of the following methods: ultrasonic peeling, dry ball milling peeling, or scraper peeling, as long as the positive electrode active material can be peeled off from the current collector under dry conditions.

[0041] In other embodiments, the homogeneous aqueous solution is prepared in step S1 as follows: According to the solid-liquid ratio of 1 kg: (5-20) L, the pretreated waste sodium ferric sulfate-based positive electrode sheet is completely immersed in deionized water at 25-40℃, stirred at 50-100 rpm for 20-30 min, then heated to 60-80℃, stirred at 150-200 rpm for 90-120 min, cooled to 35-45℃, stirred at 50-100 rpm for 20-30 min, and the current collector is removed to obtain a homogeneous aqueous solution.

[0042] The aforementioned technical solutions provide two leaching methods for cathode materials: mechanical stripping of coarse powder for water-soluble impurity removal and direct leaching of electrode sheets. These methods are adaptable to different raw material scenarios, such as defective electrode sheets and mass-produced retired batteries, without requiring additional specialized equipment and can be directly integrated into existing battery material mass production lines. Furthermore, the three-stage leaching scheme with different temperatures, rotation speeds, and leaching times, employing a progressive process of low-temperature pre-dissolution, medium-temperature controllable leaching, and low-temperature steady-state homogenization, ensures that the Fe content... 3+ / Fe 2+ The active substances are fully dissolved, while avoiding the Fe caused by prolonged high-temperature leaching. 2+ Liquid-phase oxidation; staged stirring at varying speeds ensures uniform distribution of iron ions throughout the solution, eliminating localized Fe... 3+ Enrichment phenomenon, avoiding localized Fe 3+ Insufficient reduction, localized Fe 2+ The problem of uneven valence states due to excessive oxidation.

[0043] In some embodiments, in step S2, the sodium source is at least one of sodium sulfate, sodium carbonate, sodium hydroxide, sodium oxalate, and sodium nitrate.

[0044] In some embodiments, in step S2, the iron source is at least one of ferrous sulfate, ferric sulfate, ferrous sulfate monohydrate, ferrous sulfate heptahydrate, ferric oxide, and ferrous oxalate.

[0045] In some embodiments, in step S3, a pH adjuster and / or a complexing agent are added to the elemental calibration solution. The pH adjuster is used to adjust the pH of the elemental calibration solution to 2.5–6.5, and the complexing agent is used to complex the Fe in the elemental calibration solution. 3+ To form the precursor nucleus for crystallization, the amount of complexing agent used is 0%–5% of the total molar amount of iron. At least one of the pH adjuster and complexing agent must be an organic acid to ensure decomposition at a relatively low calcination temperature (300-400℃), generating sufficient reducing protective gases such as CO and H2 to further promote Fe crystallization. 3+ Complete reduction. The pH of the quasi-controlled system was adjusted to a weakly acidic range of 2.5–6.5, which is the range for Fe. 2+ The steady-state optimal range can suppress Fe from the root cause. 2+ Hydrolysis and oxidation, while significantly improving the carbon source's affinity for Fe. 3+ The reduction efficiency; using a complexing agent to complex highly active free Fe in the system. 3+ Weakening Fe 3+ Aggregation inertness, activation of Fe 3+ Reaction sites, reduced reduction difficulty, and facilitate Fe 3+ Completely converted to Fe 2+ .

[0046] In some embodiments, the pH adjuster is at least one of citric acid, sulfuric acid, oxalic acid, malic acid, tartaric acid, malonic acid, succinic acid, vitamin C, and acetic acid.

[0047] The aforementioned pH adjuster can stabilize the elemental calibration solution within a weakly acidic range suitable for controlling the iron valence state, while also taking into account the Fe... 3+ Deep reduction and Fe 2+ Antioxidant protection. The sulfuric acid and sulfate system are homologous, free of impurity ions, allowing for precise control of system acidity and maximizing the retention of Fe. 3+ Reducing activity; Acetic acid possesses excellent pH buffering properties, which can prevent acidity drift during the process and effectively inhibit Fe. 2+ Oxidation. Citric acid has both acid-regulating and selective complexing properties, and can disperse Fe. 3+ Aggregation and clustering, lowering the reduction barrier, and enhancing Fe 3+ Completeness of reduction; oxalic acid has weak reducing properties and can assist in the reduction of residual Fe. 3+ The aforementioned pH adjuster can be completely pyrolyzed at high temperatures without leaving any impurities, and can effectively stabilize Fe. 2+ / Fe 3+ Mixed valence states significantly improve the structural uniformity and electrochemical stability of recycled materials.

[0048] In some embodiments, the complexing agent is at least one of ethylenediaminetetraacetic acid, sodium citrate, citric acid, vitamin C, ammonium oxalate, ammonia, gluconic acid, and lactic acid.

[0049] The aforementioned complexing agents can precisely control the form of iron ions in the liquid phase, synergistically achieving Fe 3+ Fully reduced with Fe 2+ Stable retention. Ethylenediaminetetraacetic acid, sodium citrate, citric acid, and vitamin C can effectively complex free iron ions, break up iron ion clusters, eliminate reduction blind zones, and enhance Fe... 3+ The homogeneity and thoroughness of reduction are improved. Ammonium oxalate can assist in the directional nucleation of precursors and optimize crystal morphology; trace amounts of ammonia can fine-tune the liquid phase microenvironment, adapting it to the complexation reaction system. Glucolic acid and lactic acid are sodium-free complexing agents, which will not interfere with the sodium-iron stoichiometric ratio of the system and can selectively activate Fe. 3+ At the same time in Fe 2+ A protective structure is formed on the surface to inhibit its oxidation and failure.

[0050] In some embodiments, in step S3, the carbon source is at least one of maltodextrin, glucose, acetylene black, Ketjen black, pectin, and lignin.

[0051] The aforementioned carbon sources possess both gradient reduction and conductive modification effects. Maltodextrin, glucose, pectin, and lignin are weakly reducing organic carbon sources that can gently and controllably reduce Fe in the system. 3+ Gradient reduction to Fe2+ This process avoids excessive reduction that generates impurities, effectively stabilizes the mixed valence state of iron, and forms a uniform and dense in-situ carbon coating layer after high-temperature pyrolysis, repairing lattice defects in the material. Acetylene black and Ketjen black are highly conductive carbon materials that can be uniformly dispersed in the precursor system to construct a three-dimensional continuous conductive network, improving electron conduction efficiency while blocking trace amounts of oxygen and inhibiting the formation of new Fe. 2+ Oxidation side reactions occur. The above-mentioned carbon sources have good synergy and leave no residue after pyrolysis, which can optimize the microstructure of the material, reduce electrode polarization, and significantly improve the structural stability, electrochemical cycle performance, and rate performance of the regenerated cathode material.

[0052] In some embodiments, in step S3, the ultrasonic frequency for ultrasonic stirring and mixing is 15-30 kHz, the stirring speed is 200-300 rpm, and the ultrasonic stirring time is 10-20 min.

[0053] Ultrasonic coupled mechanical stirring can completely disperse carbon source and carbon nanotube aggregates, ensuring uniform dispersion of the reduced carbon component throughout the liquid phase system. This achieves zero-distance contact between iron ions and the reducing active sites across the entire system, eliminating localized carbon source gaps in the liquid phase and resolving the issue of localized Fe degradation in traditional processes. 3+ The problem of inaccessibility to reducing agents and reduction residues must be addressed to ensure that all Fe in the system... 3+ All can be fully and uniformly reduced to Fe 2+ .

[0054] In some embodiments, in step S4, the particle size D50 of the recycled slurry is controlled to be 0.2 to 2 μm, and the particle size D90 is controlled to be ≤10 μm.

[0055] By precisely controlling the particle size range of the slurry through wet grinding, spherical precursor particles with a narrow particle size distribution are formed, resulting in highly uniform precursor particle size. This ensures that the particles are heated and have consistent contact with the atmosphere during subsequent sintering, preventing the formation of Fe2+ particles within large particles. 3+ Uneven heating and incomplete reduction, while preventing Fe from forming on the surface of small particles. 2+ It is oxidized by trace amounts of oxygen.

[0056] In some embodiments, in step S5, the inlet air temperature of the spray dryer is 180–260°C, and the outlet air temperature is 80–120°C.

[0057] In some embodiments, in step S5, the inert atmosphere is nitrogen or a mixture of nitrogen and hydrogen, with a nitrogen volume fraction of 92% to 99.999%; or, the inert atmosphere is argon or a combination of argon and hydrogen, with an argon volume fraction of 92% to 99.999%. Using an inert mixed atmosphere of nitrogen and hydrogen (oxygen content ≤10ppm), or an inert mixed atmosphere of argon and hydrogen (oxygen content ≤10ppm), the weak reducing property of hydrogen can suppress Fe. 2+Oxidation simultaneously achieves crystal phase reconstruction, carbon layer densification, and valence state locking.

[0058] Sodium-based ferric sulfate cathode material was prepared using the above method, and its general formula is Na. x Fe y (SO4) z ·Cw, where 1≤x≤2, 1≤y≤2, and satisfies x+2y=2z, C is the mass fraction of carbon content, and w ranges from 1% to 5%.

[0059] To more effectively illustrate the technical solution of the present invention, several specific embodiments will be described below.

[0060] Example 1: Add pH adjuster and complexing agent to elemental calibration solution, then add single-walled carbon nanotubes. The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a pouch sodium-ion battery that has failed cycling. The positive electrode active material accounts for 80% of the mass of the positive electrode sheet. After it is completely discharged, it is disassembled in a dry room with a dew point ≤ -40℃ to obtain the waste sodium iron sulfate-based positive electrode sheet. The chemical formula of the active material of the electrode sheet is Na after XPS and ICP-OES detection. 1.25 Fe 0.95 (SO4) 1.7 •Cw (where C is carbon and w is 1.3%), with iron having a +3 valence of 26%, is a typical non-stoichiometric material with a mixed +2 / +3 valence state. 1.2 kg of waste sodium ferric sulfate-based positive electrode sheet was weighed and placed in a synergistic activation treatment at 50℃ and a 30kHz ultrasonic field combined with a 2.45GHz microwave field for 20 min. The activated waste positive electrode sheet was then completely immersed in 15 L of deionized water at 30℃, stirred at 80 rpm for 25 min, then heated to 70℃ and stirred at 160 rpm for 100 min, then cooled to 40℃ and stirred at 80 rpm for 200 min. After leaching, the current collector was removed, and the liquid was filtered through a 200-mesh sieve to separate clean, undamaged aluminum foil current collector and leachate. The positive electrode active material dissolution rate was tested to reach 99.5%, i.e., 955.2 g of carbon-containing positive electrode active material and 942.782 g of Na were dissolved. 1.25 Fe 0.95 (SO4) 1.7 .

[0061] (2) The sodium and iron elements in the above leachate were quantitatively detected by ICP-OES, according to the target product of 3.846 mol Na. 1.5 Fe(SO4) 1.75To achieve the stoichiometric ratio, 61.151 g of sodium carbonate (sodium source) and 53.464 g of ferrous sulfate heptahydrate (iron source and sulfur source) were added to the leachate and stirred until completely dissolved to obtain the elemental calibration solution. The sodium-iron molar ratio in the calibrated solution was 1.55:1.

[0062] (3) Add malonic acid to the element calibration solution as a pH adjuster to adjust the pH value of the element calibration solution to 4.0. Add 11.135g of citric acid as a complexing agent, the amount of complexing agent added is 1.5% of the molar amount of iron in the element calibration solution, and stir for 20min until completely dissolved. Then, according to the mass fraction of carbon in the final obtained cathode material being 3.0%, add 265mL of single-walled carbon nanotube aqueous slurry with a solid content of 11% to the element calibration solution, and then place it under ultrasonic stirring at a frequency of 20kHz and a stirring speed of 220rpm for 15min to obtain the regeneration precursor solution.

[0063] (4) The regenerated precursor liquid is fed into a sand mill for wet grinding. The particle size D50 of the slurry after grinding is controlled to be 0.6 μm and D90 to be 3.0 μm. The solid content of the slurry is adjusted to 15% to obtain the regenerated slurry.

[0064] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 210℃ and the outlet air temperature to 95℃ to obtain precursor powder; place the precursor powder in a pusher kiln, and under the protection of nitrogen inert atmosphere with oxygen content ≤20ppm, raise the temperature to 350℃ at a heating rate of 2.0℃ / min, hold for sintering for 20h, and cool naturally to room temperature with the furnace; after crushing and sieving through a 300-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0065] Example 2: Add pH adjuster and complexing agent to elemental calibration solution, then add maltodextrin carbon source. The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a pouch sodium-ion battery that has failed cycling. The positive electrode active material accounts for 80% of the mass of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheets. The chemical formula of the active material of the electrode sheet is Na after XPS and ICP-OES detection. 1.13 Fe 0.9 (SO4) 1.7•Cw (where C is carbon and w is 1.2%), with iron having a +3 valence of 52%, is a typical non-stoichiometric material with a mixed +2 / +3 valence state. Waste sodium ferric sulfate-based positive electrode sheets were subjected to synergistic activation treatment at 40℃ and a 20kHz ultrasonic field and a 2.45GHz microwave field for 10 minutes. The activated waste positive electrode sheets were then mechanically peeled off using a dry ball milling method to completely remove the positive electrode active material from the aluminum foil current collector, yielding coarse positive electrode powder. 1.0 kg of coarse positive electrode powder was weighed and added to 5 L of deionized water at 25°C. The mixture was stirred at 100 rpm for 20 min, then heated to 60°C and stirred at 250 rpm for 90 min. The temperature was then lowered to 35°C and stirred at 50 rpm for 20 min. After leaching, the leachate was allowed to settle for 30 min and filtered through a 300-mesh sieve to remove aluminum residue, yielding a homogeneous aqueous solution containing sodium, iron, and sulfate. The active material dissolution rate was measured to be 99.4%, meaning 994 g of carbon-containing positive electrode active material and 982.072 g of Na were dissolved. 1.13 Fe 0.9 (SO4) 1.7 .

[0066] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements using ICP-OES, according to the target product of 4.099 mol Na. 1.6 Fe(SO4) 1.8 To achieve the stoichiometric ratio, 106.452 g of sodium carbonate (sodium source) and 113.969 g of ferrous sulfate heptahydrate (iron source and sulfur source) were added to the homogeneous aqueous solution and stirred until completely dissolved to obtain the element calibration solution. The sodium-iron molar ratio in the calibrated solution was 1.62:1.

[0067] (3) Add succinic acid as a pH adjuster to the element calibration solution to adjust the pH value to 3.0. Add 1.77 mL of 85 wt% lactic acid liquid as a complexing agent. The amount of complexing agent added is 0.5% of the molar amount of iron in the element calibration solution. Stir for 20 min until completely dissolved. Then, according to the mass fraction of carbon in the final cathode material being 2.0%, add 22.217 g of maltodextrin to the element calibration solution. Then, place it under ultrasonic stirring at a frequency of 15 kHz and a stirring speed of 200 rpm for 10 min to obtain the regeneration precursor solution.

[0068] (4) The regenerated precursor liquid is fed into a sand mill for wet grinding. The particle size of the slurry after grinding is controlled to be 0.2 μm for D50 and 4.0 μm for D90. The solid content of the slurry is adjusted to 10% to obtain a homogeneous regenerated slurry.

[0069] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 180℃ and the outlet air temperature to 80℃ to obtain spherical precursor powder; place the precursor powder in a tube furnace, and under the protection of an inert atmosphere (composed of 92% nitrogen and 8% hydrogen by volume) with an oxygen content of ≤20ppm, raise the temperature to 350℃ at a heating rate of 2.0℃ / min, hold for sintering for 12h, and then let it cool naturally to room temperature with the furnace; after crushing and sieving through a 300-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0070] Example 3: Add pH adjuster and complexing agent to elemental calibration solution, then add single-walled carbon nanotubes. The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a pouch sodium-ion battery that has failed cycling. The positive electrode active material accounts for 80% of the mass of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheets. The chemical formula of the active material of the electrode sheet is Na after XPS and ICP-OES detection. 1.23 Fe 0.98 (SO4) 1.65 •Cw (where C is carbon and w is 1.2%), with iron having a +3 valence of 11%, is a typical non-stoichiometric material with a mixed +2 / +3 valence state. Waste sodium ferric sulfate-based cathode sheets were subjected to synergistic activation treatment at 60℃ and a 40kHz ultrasonic field and a 2.45GHz microwave field for 30 minutes. The activated waste cathode sheets were then mechanically peeled off using a dry ball milling method to completely remove the cathode active material from the aluminum foil current collector, yielding coarse cathode powder. 1 kg of coarse positive electrode powder was weighed and added to 20 L of deionized water at 40 °C. The mixture was stirred at 150 rpm for 30 min, then heated to 80 °C and stirred at 300 rpm for 120 min. The temperature was then lowered to 45 °C and stirred at 100 rpm for 30 min. After leaching, the leachate was allowed to settle for 30 min and filtered through a 300-mesh sieve to remove aluminum residue, yielding a homogeneous aqueous solution containing sodium, iron, and sulfate. The active material dissolution rate was measured to be 99.8%, meaning 998 g of carbon-containing positive electrode active material and 986.024 g of Na were dissolved. 1.23 Fe 0.98 (SO4) 1.65 .

[0071] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements using ICP-OES, according to the target product of 4.082 mol Na. 1.4 Fe(SO4) 1.7To obtain the stoichiometric ratio, 47.597g of sodium carbonate (sodium source), 22.699g of ferrous sulfate heptahydrate (iron source and sulfur source), and 12.257g of 98% concentrated sulfuric acid (sulfur source) were added to the solution and stirred until completely dissolved to obtain the element calibration solution. The sodium-iron molar ratio in the calibrated solution was 1.45:1.

[0072] (3) Oxalic acid was added to the element calibration solution as a pH adjuster to adjust the pH value of the element calibration solution to 5.0. 36.75g of gluconic acid was added as a complexing agent. The amount of complexing agent added was 5.0% of the molar amount of iron in the element calibration solution. The mixture was stirred for 20min until completely dissolved. Subsequently, according to the mass fraction of carbon in the final cathode material being 5.0%, 509mL of single-walled carbon nanotube slurry with a solid content of 10wt% was added to the element calibration solution. The mixture was then ultrasonically stirred for 20min at a frequency of 30kHz and a stirring speed of 300rpm to obtain the regeneration precursor solution.

[0073] (4) The regenerated precursor liquid is fed into a sand mill for wet grinding. The particle size of the slurry after grinding is controlled to be 2.0 μm for D50 and 8.0 μm for D90. The solid content of the slurry is adjusted to 20% to obtain a homogeneous regenerated slurry.

[0074] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 260℃ and the outlet air temperature to 120℃ to obtain spherical precursor powder; place the precursor powder in a tube furnace, and under the protection of an inert atmosphere (composed of 95% nitrogen and 5% hydrogen by volume) with an oxygen content of ≤20ppm, raise the temperature to 380℃ at a heating rate of 1.0℃ / min, hold for sintering for 8h, and then let it cool naturally to room temperature with the furnace; after crushing and sieving through a 300-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0075] Example 4: Add pH adjuster to elemental calibration solution, then add single-walled carbon nanotubes. The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a pouch sodium-ion battery that has failed cycling. The positive electrode active material accounts for 80% of the mass of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheets. The chemical formula of the active material of the electrode sheet is Na after XPS and ICP-OES detection. 0.88 Fe 0.95 (SO4) 1.85•Cw (where C is carbon and w is 2.6%), with 96% of the iron element having a +3 valence, is a typical non-stoichiometric material with a mixed +2 / +3 valence state. 1.2 kg of waste sodium ferric sulfate-based positive electrode sheet was weighed and placed in a synergistic activation treatment at 50℃ and a 30kHz ultrasonic field combined with a 2.45GHz microwave field for 20 min. The activated waste positive electrode sheet was then completely immersed in 5 L of deionized water at 25℃, stirred at 50 rpm for 25 min, then heated to 60℃ and stirred at 150 rpm for 90 min, then cooled to 35℃ and stirred at 50 rpm for 20 min. After leaching, the current collector was removed, and the leachate was filtered through a 200-mesh sieve to separate clean, undamaged aluminum foil current collector and homogeneous aqueous solution. The active material dissolution rate was tested to reach 99.5%, with 955.2 g of carbon-containing positive electrode active material and 930.365 g of Na dissolved. 0.88 Fe 0.95 (SO4) 1.85 .

[0076] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements using ICP-OES, according to the target product of 3.706 mol Na. 1.8 Fe(SO4) 1.9 To obtain the stoichiometric ratio, 188.561 g of sodium carbonate (sodium source) and 51.520 g of ferrous sulfate heptahydrate (iron source and sulfur source) were added to the solution and stirred until completely dissolved to obtain the element calibration solution. The sodium-iron molar ratio in the calibrated solution was 1.84:1.

[0077] (3) Add a mixture of oxalic acid and citric acid in a mass ratio of 2:1 to the element calibration solution as a pH adjuster to adjust the pH value of the element calibration solution to 3.0. Then, according to the mass fraction of carbon element in the final obtained positive electrode material being 4.0%, add 271 mL of single-walled carbon nanotube slurry with a solid content of 15 wt% to the element calibration solution. Then, place it under ultrasonic stirring at a frequency of 20 kHz and a stirring speed of 220 rpm for 15 min to obtain the regeneration precursor solution.

[0078] (4) The regenerated precursor liquid is fed into a ball mill, using zirconia balls as the grinding medium, with a ball-to-material ratio of 5:1, and wet ball milling for 2 hours. The particle size of the slurry after grinding is controlled to be D50 of 1.1 μm and D90 of 4.2 μm. The solid content of the slurry is adjusted to 40% to obtain a homogeneous regenerated slurry.

[0079] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 230℃ and the outlet air temperature to 105℃ to obtain precursor powder; place the precursor powder in a pusher kiln, and under the protection of an argon inert atmosphere with an oxygen content of ≤20ppm, raise the temperature to 330℃ at a heating rate of 1.0℃ / min, hold for sintering for 20h, and then cool naturally to room temperature with the furnace; after crushing and sieving through a 250-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0080] Example 5: Add pH adjuster and complexing agent to elemental calibration solution, then add glucose carbon source and single-walled carbon nanotubes. The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a pouch sodium-ion battery that has failed cycling. The positive electrode active material accounts for 80% of the mass of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheets. The chemical formula of the active material of the electrode sheet is Na after XPS and ICP-OES detection. 1.18 Fe 0.98 (SO4) 1.92 •Cw (where C is carbon and w is 2.6%), with 72% of the iron element having a +3 valence, is a typical non-stoichiometric material with a mixed +2 / +3 valence state. 1 kg of waste sodium ferric sulfate-based positive electrode sheet was weighed and placed in a synergistic activation treatment at 50℃ and a 30kHz ultrasonic field combined with a 2.45GHz microwave field for 20 min. The activated waste positive electrode sheet was then completely immersed in 20 L of deionized water at 40℃, stirred at 100 rpm for 30 min, then heated to 80℃ and stirred at 200 rpm for 120 min, then cooled to 45℃ and stirred at 100 rpm for 30 min. After leaching, the current collector was removed, and the leachate was filtered through a 200-mesh sieve to separate clean, undamaged aluminum foil current collector and homogeneous aqueous solution. The active material dissolution rate was tested to reach 99.7%, i.e., 957.1 g of carbon-containing positive electrode active material and 932.234 g of Na were dissolved. 1.18 Fe 0.98 (SO4) 1.92 .

[0081] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements by ICP-OES. According to the stoichiometric ratio of the target product 3.5 mol Na2Fe(SO4)2, 140.41 g sodium carbonate (sodium source), 28.08 g anhydrous sodium sulfate (sodium source and sulfur source), 19.46 g ferrous sulfate heptahydrate (iron source and sulfur source) and 1.21 g 98% concentrated sulfuric acid (sulfur source) were added to the solution and stirred until completely dissolved to obtain the element calibration solution. The sodium-iron molar ratio in the calibrated solution was 2.05:1.

[0082] (3) Citric acid was added to the element calibration solution as a pH adjuster to adjust the pH value of the element calibration solution to 5.0. 34.3g of gluconic acid was added as a complexing agent. The amount of complexing agent added was 5.0% of the molar amount of iron in the element calibration solution. The mixture was stirred for 20min until completely dissolved. Subsequently, according to the mass fraction of carbon in the final cathode material being 5.0%, 13.54g of glucose and 255mL of single-walled carbon nanotube slurry with a solid content of 15wt% were added to the element calibration solution. The mixture was then ultrasonically stirred for 15min at a frequency of 20kHz and a stirring speed of 220rpm to obtain the regeneration precursor solution.

[0083] (4) The regenerated precursor liquid is fed into a ball mill, using zirconia balls as the grinding medium, with a ball-to-material ratio of 5:1, and wet ball milling for 2 hours. The particle size of the slurry after grinding is controlled to be D50 of 1.0 μm and D90 of 3.8 μm. The solid content of the slurry is adjusted to 20% to obtain a homogeneous regenerated slurry.

[0084] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 230℃ and the outlet air temperature to 105℃ to obtain precursor powder; place the precursor powder in a pusher kiln, and under the protection of an inert atmosphere with an oxygen content of ≤20ppm (composed of 92% argon and 8% hydrogen by volume), raise the temperature to 380℃ at a heating rate of 2℃ / min, hold for sintering for 6h, and then cool naturally to room temperature with the furnace; after crushing and sieving through a 250-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0085] Example 6: Adding multi-walled carbon nanotubes and glucose to mechanically exfoliated coarse powder and elemental calibration solution The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a soft-pack sodium-ion battery that has failed in cycles. The mass of the positive electrode active material in the battery accounts for 80% of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheet. The chemical formula of the active material of the electrode sheet is Na1 by XPS and ICP-OES detection. 72 Fe 0.99 (SO4) 1.9•Cw (where C is carbon and w is 2.4%), with iron having a +3 valence of 10%, is a typical non-stoichiometric material with a mixed +2 / +3 valence state. Waste sodium ferric sulfate-based positive electrode sheets were subjected to synergistic activation treatment at 50℃ and a 30kHz ultrasonic field and a 2.45GHz microwave field for 20 minutes. The activated waste positive electrode sheets were then mechanically peeled off using a dry ball milling method to completely remove the positive electrode active material from the aluminum foil current collector, yielding coarse positive electrode powder. 1 kg of coarse positive electrode powder was weighed and added to 12 L of deionized water at 30 °C. The mixture was stirred at 120 rpm for 25 min, then heated to 70 °C and stirred at 260 rpm for 100 min. The temperature was then lowered to 40 °C and stirred at 60 rpm for 25 min. After leaching, the leachate was allowed to settle for 30 min and filtered through a 300-mesh sieve to remove aluminum residue. A homogeneous aqueous solution containing sodium, iron, and sulfate was obtained. The dissolution rate of the active material was measured to be 99.6%, which means that 996 g of carbon-containing positive electrode active material and 972 g of Na1 were dissolved. 72 Fe 0.99 (SO4) 1.9 .

[0086] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements by ICP-OES. According to the stoichiometric ratio of the target product 3.505 mol Na2Fe(SO4)2, 44.66 g sodium carbonate (sodium source), 22.33 g anhydrous sodium sulfate (sodium source and sulfur source), 9.73 g ferrous sulfate heptahydrate and 15.48 g 98% concentrated sulfuric acid were added to the solution and stirred until completely dissolved to obtain the element calibration solution. The sodium-iron molar ratio in the calibrated solution was 2.05:1.

[0087] (3) According to the mass fraction of carbon element in the final obtained positive electrode material being 2.5%, 166 mL of multi-walled carbon nanotube aqueous slurry with a solid content of 10 wt% and 8.81 g of glucose were added to the element calibration solution (the carbon residue in multi-walled carbon nanotube aqueous slurry and glucose was 2:1 according to the mass fraction of carbon element in the final obtained positive electrode material). Then, the solution was ultrasonically stirred for 15 min at a frequency of 20 kHz and a stirring speed of 220 rpm to obtain the regeneration precursor solution.

[0088] (4) The regenerated precursor liquid is fed into a sand mill for wet grinding. The particle size of the slurry after grinding is controlled to be 0.9 μm for D50 and 3.6 μm for D90. The solid content of the slurry is adjusted to 15% to obtain a homogeneous regenerated slurry.

[0089] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 220℃ and the outlet air temperature to 100℃ to obtain spherical precursor powder; place the precursor powder in a tube furnace, and under the protection of an inert atmosphere (composed of 95% argon and 5% hydrogen by volume) with an oxygen content of ≤20ppm, raise the temperature to 350℃ at a heating rate of 3℃ / min, hold for sintering for 8h, and then let it cool naturally to room temperature with the furnace; after crushing and sieving through a 300-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0090] Example 7: Adding glucose carbon source to the positive electrode plate during water immersion and elemental calibration solution The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a pouch sodium-ion battery that has failed cycling. The positive electrode active material accounts for 80% of the mass of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheets. The chemical formula of the active material of the electrode sheet is Na after XPS and ICP-OES detection. 1.88 Fe(SO4)2·Cw (where C is carbon and w is 2.6%) has an iron +3 valence of 12%, making it a typical non-stoichiometric material with a mixed +2 / +3 valence state. 1.2 kg of waste sodium ferric sulfate-based positive electrode sheet was weighed and subjected to synergistic activation treatment in a 50℃, 30kHz ultrasonic field and a 2.45GHz microwave field for 20 min. The activated waste positive electrode sheet was then completely immersed in 15L of deionized water at 30℃ and stirred at 80 rpm for 25 min. The temperature was then raised to 70℃ and stirred at 160 rpm for 100 min. The temperature was then lowered to 40℃ and stirred at 80 rpm for 25 min. After leaching, the current collector was removed, and the leachate was filtered through a 200-mesh sieve to separate the contents, yielding a clean, undamaged aluminum foil current collector and a homogeneous aqueous solution. The active material dissolution rate was tested and found to be 99.8%, meaning 958g of carbon-containing positive electrode active material and 933.17g of Na were dissolved. 1.88 Fe(SO4)2.

[0091] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements by ICP-OES. According to the stoichiometric ratio of the target product Na2Fe(SO4)2, 28.870g of sodium carbonate (sodium source) and 12.52g of oxalic acid were added to the solution and stirred until completely dissolved to obtain the element calibration solution. The sodium-iron molar ratio in the calibrated solution was 2.05:1.

[0092] (3) According to the mass fraction of carbon element in the final obtained positive electrode material being 2.0%, 19g of glucose was added to the element calibration solution, and then ultrasonically stirred for 15min at a frequency of 20kHz and a stirring speed of 220rpm to obtain the regeneration precursor solution.

[0093] (4) The regenerated precursor liquid is fed into a ball mill, using zirconia balls as the grinding medium, with a ball-to-material ratio of 5:1, and wet ball milling for 2 hours. The particle size D50 of the slurry after grinding is controlled to be 1.1 μm and D90 to be 4.2 μm. The solid content of the slurry is adjusted to 18% to obtain a homogeneous regenerated slurry.

[0094] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 230℃ and the outlet air temperature to 105℃ to obtain precursor powder; place the precursor powder in a pusher kiln, and under the protection of an inert atmosphere (composed of 95% nitrogen and 5% hydrogen by volume) with an oxygen content of ≤20ppm, raise the temperature to 380℃ at a heating rate of 2℃ / min, hold for sintering for 6h, and then cool naturally to room temperature with the furnace; after crushing and 250 mesh sieve, obtain sodium-based iron sulfate cathode material.

[0095] Example 8: Adding pectin to elemental calibration solution The method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries in this embodiment is as follows: (1) Take a soft-pack sodium-ion battery that has failed in cycles. The mass of the positive electrode active material in the battery accounts for 80% of the positive electrode sheet. After complete discharge, disassemble it in a dry room with a dew point ≤ -40℃ to obtain waste sodium iron sulfate-based positive electrode sheet. The chemical formula of the active material of the electrode sheet is Na1 by XPS and ICP-OES detection. 65 Fe(SO4)2·Cw (where C is carbon and w is 2.0%) has an iron +3 valence ratio of 35%, making it a typical non-stoichiometric material with a mixed +2 / +3 valence state. Waste sodium ferric sulfate-based cathode sheets were subjected to synergistic activation treatment at 50℃ and a 30kHz ultrasonic field combined with a 2.45GHz microwave field for 20 minutes. The activated waste cathode sheets were then mechanically peeled off using a dry ball milling method to completely remove the active material from the aluminum foil current collector, yielding coarse cathode powder. 1 kg of coarse positive electrode powder was weighed and added to 13 L of deionized water at 30 °C. The mixture was stirred at 120 rpm for 25 min, then heated to 70 °C and stirred at 260 rpm for 100 min. The temperature was then lowered to 40 °C and stirred at 60 rpm for 25 min. After leaching, the leachate was allowed to settle for 30 min and filtered through a 300-mesh sieve to remove aluminum residue. A homogeneous aqueous solution containing sodium, iron, and sulfate was obtained. The dissolution rate of the active material was measured to be 99.7%, which means that 997 g of carbon-containing positive electrode active material and 977 g of Na1 were dissolved. 65 Fe(SO4)2.

[0096] (2) The above homogeneous aqueous solution was subjected to quantitative detection of sodium and iron elements using ICP-OES, according to the target product of 3.417 mol Na. 1.98 Fe 1.2 (SO4)2.1 To achieve the stoichiometric ratio, 56.24 g of sodium carbonate, 112.48 g of anhydrous sodium sulfate (sodium and sulfur sources), 190.16 g of ferrous sulfate heptahydrate (iron and sulfur sources), and 29.53 g of 98% concentrated sulfuric acid (sulfur source) were added to the solution. The mixture was stirred until completely dissolved to obtain the element calibration solution. After calibration, the sodium-iron molar ratio in the solution was 2.02:1.

[0097] (3) According to the mass fraction of carbon element in the final obtained positive electrode material being 2.8%, 206 mL of pectin aqueous solution with a concentration of 15 wt% was added to the element calibration solution, and then ultrasonically stirred for 15 min at a frequency of 20 kHz and a stirring speed of 220 rpm to obtain the regeneration precursor solution.

[0098] (4) The regenerated precursor liquid is fed into a sand mill for wet grinding. The particle size of the slurry after grinding is controlled to be 0.8 μm for D50 and 3.5 μm for D90. The solid content of the slurry is adjusted to 14% to obtain a homogeneous regenerated slurry.

[0099] (5) Spray dry and granulate the recycled slurry, control the inlet air temperature to 220℃ and the outlet air temperature to 100℃ to obtain spherical precursor powder; place the precursor powder in a tube furnace, and under the protection of an inert atmosphere (composed of 95% nitrogen and 5% hydrogen by volume) with an oxygen content of ≤20ppm, raise the temperature to 350℃ at a heating rate of 2.5℃ / min, hold for sintering for 8h, and then let it cool naturally to room temperature with the furnace; after crushing and sieving through a 300-mesh sieve, obtain sodium-based iron sulfate cathode material.

[0100] Comparative Example 1 This comparative example uses pure-phase sodium ferrous sulfate cathode material (Na) purchased from the market. x Fe(SO4) x / 2+1 ·Cw, where 1≤x≤2, C is carbon, and w takes values ​​ranging from 3.0%.

[0101] Comparative Example 2 The difference between this comparative example and Example 1 is that: Before performing step (3), add sodium sulfite, a reducing agent, to the elemental calibration solution. The amount added is equal to the amount of Fe in the elemental calibration solution. 3+ 1.08 times the molar amount, stirred at room temperature for 25 min, to complete the Fe... 3+ to Fe 2+ Complete reduction, resulting in SO4. 2- No impurity ions remain, and the reduced calibration solution is obtained.

[0102] In step (3), carbon source Ketjen black is added to the reduced calibration solution according to the mass fraction of carbon element in the final obtained cathode material being 1.5%, and stirred for 35 minutes until it is completely dispersed and uniform to obtain the regenerated precursor solution.

[0103] The other steps (1), (2), (4), and (5) are the same as in Example 1.

[0104] Comparative Example 3 The difference between this comparative example and Example 2 is that: Before performing step (3), the element calibration solution is fed into the electrolytic cell, with graphite as the cathode and titanium as the anode, and the electrolysis voltage is controlled at 1.3V and the current density at 8mA / cm². 2 Electrolysis for 45 minutes, and Fe was confirmed by potential monitoring. 3+ At the reduction endpoint (reduction rate ≥ 99%), no chemical reagents are needed to obtain the reduced calibration solution. Perform step (3) on the reduced calibration solution.

[0105] The remaining steps and conditions are the same as in Example 2.

[0106] Comparative Example 4 The difference between this comparative example and Example 2 is that: Before performing step (2), iron powder is added to the homogeneous aqueous solution. The amount of iron powder added is Fe 3+ Add 1.15 times the molar amount, then add sulfuric acid to adjust the pH to approximately 5.0, and stir at 150 rpm for 35 minutes to complete the Fe... 3+ to Fe 2+ The reduction solution was filtered through a 150-mesh sieve to remove excess iron powder, resulting in a reduced aqueous solution. Then, step (2) was performed on the reduced aqueous solution.

[0107] The remaining steps and conditions are the same as in Example 2.

[0108] Performance testing: (1) Using the sodium-based ferric sulfate cathode materials prepared in Examples 1-8 and the sodium ferrous sulfate cathode material of Comparative Example 1 as samples, X-ray diffraction analysis was performed, and the results are as follows: Figure 1 As shown. From Figure 1 It can be seen that the XRD diffraction peaks of the sodium-based ferrous sulfate cathode materials prepared in Examples 1-8 are sharp, with narrow half-peak widths and standard peak positions. The commercially available pure-phase sodium ferrous sulfate cathode materials have no extra impurity peaks, flat baselines, and represent complete pure-phase sodium ferrous sulfate crystals with complete lattice, no distortion, and no impurity phases such as iron oxide, sodium sulfate, or elemental iron, exhibiting superior crystallinity.

[0109] (2) Using the sodium-based ferric sulfate cathode material prepared in Example 1 as a sample, the microstructure and composition information of the material were observed by scanning the sample surface with an electron beam. The obtained SEM image is shown below. Figure 2As shown in the SEM image (magnified 50,000 times) of the regenerated sodium-based ferric sulfate cathode material from Example 1, it can be clearly observed that slender, curved multi-walled carbon nanotubes are uniformly interspersed between spherical nanoscale NFS active grains. The carbon nanotubes with uniform diameter overlap each other to form a complete three-dimensional conductive network. The size of the active primary grains is concentrated in the range of 50-120 nm, with regular and rounded grain morphology and intact crystal skeleton. There are no large number of broken and irregularly shaped particles, indicating that the microwave-ultrasonic synergistic leaching and wet sand milling process has completely removed the original PVDF adhesive layer of the waste electrode, completely removed the organic residue, and the grain boundaries are clear. The overall powder dispersion is good, with only a small amount of soft agglomeration of grains and slight entanglement of carbon nanotubes in some areas, which is a common phenomenon in wet spray granulation. This carbon composite microstructure can effectively reduce the interfacial impedance of particles, laying the microstructural foundation for the excellent rate capability and cycle performance of the material.

[0110] (3) The sodium-based ferric sulfate cathode materials prepared in Examples 1-8 and the sodium ferrous sulfate cathode materials in Comparative Examples 1-4 were used as samples for electrical performance testing. Specifically, the sample, conductive agent Super P, and binder PVDF were mixed in a weight ratio of 8:1:1 to prepare a cathode slurry, which was coated on one side of the aluminum foil surface and dried to obtain a cathode sheet. The cathode sheet was then assembled into a coin cell in the order of negative electrode shell, sodium sheet, separator, electrolyte, cathode sheet, gasket, spring sheet, and cathode shell. The electrolyte was 1M NaClO4, the solvent was PC, and the separator was GF / C type glass fiber. The coin cell was placed in the Blue Electric test system for electrical performance testing. The electrical performance test parameters were set as follows: voltage range 2.0V-4.3V, and capacity test was performed in the first cycle with 0.1C / 0.1C charge and discharge (the test results are as follows). Figure 3 (As shown in Table 1), and then the rate performance was evaluated by charge / discharge tests at 0.2C / 0.2C, 0.5C / 0.5C, 1C / 1C, 2C / 2C, and 5C / 5C (test results are shown in Table 1). Figure 4 As shown), the cycling performance was finally evaluated by cycling 100 times at 0.2C / 0.2C (the test results are as follows). Figure 5 (as shown in Table 1).

[0111] Table 1 Combining Table 1 and Figure 3 The data shows that, under test conditions of 2.0~4.3 V and 0.1C, the initial charge-discharge curves of the sodium-based ferric sulfate material in Example 1 and the cathode material in Comparative Example 1 show a high degree of overlap in their redox potentials, indicating that both exhibit consistent Fe content. 2+ / Fe 3+The characteristic voltage plateau proves that the main crystalline phase of the regenerated product in Example 1 is the target sodium ferric sulfate, and the electrochemical reaction mechanism is completely matched with that of commercial high-purity raw materials. The charging curves are consistent throughout, and there is no obvious irreversible voltage bulge in the low-voltage region, indicating that the regeneration process effectively removes impurities from the electrode binder, with few side reactions and low initial irreversible capacity. During the discharge process, the discharge specific capacity of Example 1 is slightly lower than that of Comparative Example 1, which is due to the slight ionic internal resistance caused by the original lattice distortion and a small amount of grain agglomeration of the waste raw materials. However, its capacity reaches more than 95% of that of the commercial sample, and the difference between the charging and discharging polarization values ​​is extremely small. It achieves excellent electronic conduction ability by relying on the multi-walled carbon nanotube conductive system, which fully verifies that this wet recycling and regeneration process can efficiently restore the electrochemical activity of the failed cathode material. The electrochemical performance of the regenerated material is highly comparable to that of the commercial raw material.

[0112] from Figure 4 As can be seen from the gradient rate performance curves, in the low rate ranges of 0.1C, 0.2C, and 0.5C, the discharge specific capacity of the recycled material in Example 1 and the commercial pure phase material in Comparative Example 1 are basically consistent, with only slight differences. This reflects that the electrochemical reaction reversibility of the recycled sample, which relies on the conductive network constructed by multi-walled carbon nanotubes, is basically on par with that of the commercial raw material under low current conditions. As the rate increases to the medium-high rates of 1C and 2C, the capacity of Example 1 is slightly lower than that of Comparative Example 1. At the high rate of 5C, the capacity difference between the two widens slightly, but Example 1 still maintains a high discharge capacity without any sudden drop in capacity. The capacity retention rate at 5C is only 3% lower than that of the commercial sample, and the overall rate retention performance is excellent. The slight decrease in capacity is due to the high solid-phase ion diffusion resistance caused by a small number of lattice defects and local grain agglomeration in the recycled material. The overall rate performance is very close to that of commercial high-purity raw materials, which fully confirms that the material prepared by this recycling process has good fast-charging performance.

[0113] Combining Table 1 and Figure 5 The data shows that in the long-cycle test at a voltage range of 2.0~4.3V and a rate of 0.2C, the capacity decay trends of the regenerated sodium ferric sulfate material in Example 1 and the commercial pure-phase material in Comparative Example 1 are both gradual and stable. There was no precipitous drop in capacity after 100 cycles, and the overall cycle stability was at the same level. The initial discharge capacity of Example 1 was slightly lower than that of Comparative Example 1, and the capacity difference between the two remained within a small range throughout the cycle. This is because the multi-walled carbon nanotube composite carbon coating structure effectively buffered the lattice stress generated by repeated insertion and extraction of sodium ions, inhibiting grain pulverization and conductive network failure. Only the trace lattice defects and local grain agglomeration of the waste raw materials made the capacity decay rate of the regenerated sample slightly higher than that of the commercial raw materials. This is sufficient to prove that the recycling and regeneration process of the present invention can efficiently repair the crystal structure of the waste failed cathode, and the long cycle life of the regenerated products can fully match that of the commercial raw materials, which has good practical application value.

[0114] The foregoing description includes examples from this specification. Of course, for the purposes of describing this specification, it is impossible to describe every conceivable combination of components or methods; however, those skilled in the art will understand that many other combinations and arrangements are possible. Therefore, this specification is intended to cover all such changes, modifications, and variations that fall within the spirit and scope of the appended claims. Furthermore, with regard to the use of the term "comprising" in the detailed description or claims, the term is intended to be inclusive in a manner similar to the term "including," as interpreted when "comprising" is used as a transitional word in the claims.

[0115] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for recovering and regenerating sodium-based ferric sulfate cathode material from spent sodium-ion batteries, characterized in that, Includes the following steps: Waste iron sulfate sodium-based positive electrode sheets were obtained by dismantling fully discharged waste sodium-ion batteries. After pretreatment, sodium iron sulfate was leached out with water, and solid-liquid separation was performed to obtain a homogeneous aqueous solution containing sodium, iron, and sulfate. The iron element in the homogeneous aqueous solution was in a mixed valence state of +2 and +3. To detect the sodium and iron content in a homogeneous aqueous solution, sodium and iron sources are added to the homogeneous aqueous solution according to a molar ratio of sodium to iron of (1.0–2.0):1, and the solution is dissolved to obtain an element calibration solution. A pH adjuster and / or a complexing agent are added to the elemental calibration solution. The pH adjuster is used to adjust the pH of the elemental calibration solution to 2.5–6.5, and the complexing agent is used to complex Fe in the elemental calibration solution. 3+ Forming a crystallization precursor core; and / or, according to the mass fraction of carbon element in the final cathode material being 1% to 5%, adding carbon nanotubes and / or carbon source, ultrasonically stirring and mixing to obtain a regenerated precursor solution; The regenerated precursor liquid was wet-milled to obtain a regenerated slurry with uniform particle size and a solid content of 10% to 40%. The recycled slurry was spray-dried and granulated, sintered at 300–400℃ for 4–24 h in an inert atmosphere, and then crushed and sieved to obtain recycled sodium ferric sulfate-based cathode material.

2. The method as described in claim 1, characterized in that, The pretreatment of the waste sodium ferric sulfate-based positive electrode sheet is as follows: The recycled waste sodium ferric sulfate-based positive electrode sheets were activated by simultaneous superposition of a 20-40 kHz ultrasonic field and a 2.45 GHz microwave field for 10-30 minutes, with the activation temperature controlled at 40-60℃.

3. The method as described in claim 2, characterized in that, The preparation method of the homogeneous aqueous solution is as follows: The active material of the positive electrode was peeled off from the pretreated waste sodium ferric sulfate-based positive electrode sheet using a mechanical stripping method to obtain coarse positive electrode powder. The coarse positive electrode powder was added to deionized water at 25-40℃ at a solid-liquid ratio of 1 kg: (5-20) L and leached at 100-150 rpm for 20-30 min. The temperature was then raised to 60-80℃ and leached at 250-300 rpm for 90-120 min. The temperature was then lowered to 35-45℃ and leached at 50-100 rpm for 20-30 min. The leachate was allowed to settle and the supernatant was collected to obtain a homogeneous aqueous solution.

4. The method as described in claim 2, characterized in that, The preparation method of the homogeneous aqueous solution is as follows: According to the solid-liquid ratio of 1 kg: (5-20) L, the pretreated waste sodium ferric sulfate-based positive electrode sheet is completely immersed in deionized water at 25-40℃, stirred at 50-100 rpm for 20-30 min, then heated to 60-80℃, stirred at 150-200 rpm for 90-120 min, cooled to 35-45℃, stirred at 50-100 rpm for 20-30 min, and the current collector is removed to obtain a homogeneous aqueous solution.

5. The method as described in claim 1, characterized in that, The sodium source is at least one selected from sodium sulfate, sodium carbonate, sodium hydroxide, sodium oxalate, and sodium nitrate; and / or, The iron source is at least one of ferrous sulfate, ferric sulfate, ferrous sulfate monohydrate, ferrous sulfate heptahydrate, ferric oxide, and ferrous oxalate.

6. The method as described in claim 1, characterized in that, The amount of the complexing agent used is 0% to 5% of the total molar amount of iron.

7. The method as described in claim 1, characterized in that, At least one of the pH adjuster and the complexing agent is an organic acid, and the pH adjuster is at least one selected from citric acid, sulfuric acid, oxalic acid, malic acid, tartaric acid, malonic acid, succinic acid, vitamin C, and acetic acid; and / or, The complexing agent is at least one of ethylenediaminetetraacetic acid, sodium citrate, citric acid, vitamin C, ammonium oxalate, ammonia, gluconic acid, and lactic acid.

8. The method as described in claim 1, characterized in that, The carbon source is at least one of maltodextrin, glucose, acetylene black, Ketjen black, pectin, and lignin.

9. The method as described in claim 1, characterized in that, The ultrasonic stirring and mixing process is performed at an ultrasonic frequency of 15–30 kHz, a stirring speed of 200–300 rpm, and a ultrasonic stirring time of 10–20 min.

10. The method as described in claim 9, characterized in that, The particle size D50 of the recycled slurry is controlled to be 0.2–2 μm, and the particle size D90 is controlled to be ≤10 μm.

11. The method as described in claim 1, characterized in that, The inlet air temperature of the spray dryer is 180-260℃, and the outlet air temperature is 80-120℃.

12. The method as described in claim 1, characterized in that, The inert atmosphere is nitrogen or a mixture of nitrogen and hydrogen, wherein the volume fraction of nitrogen is 92% to 99.999%; or, the inert atmosphere is argon or a combination of argon and hydrogen, wherein the volume fraction of argon is 92% to 99.999%.

13. A positive electrode material, characterized in that, The positive electrode material is obtained by the method described in any one of claims 1-12, and the positive electrode material is a sodium-based ferric sulfate positive electrode material with the general formula Na. x Fe y (SO4) z ·Cw, where 1≤x≤2, 1≤y≤2, and satisfies x+2y=2z, C is the mass fraction of carbon content, and w ranges from 1% to 5%.

14. A positive electrode plate, characterized in that, The positive electrode sheet includes the positive electrode material as described in claim 13.

15. A battery, characterized in that, The battery includes the positive electrode as described in claim 14.